Thirty-three-year experience on childhood poisoning - Özdemir, Ramazan; Bayrakcı, Benan; Tekşam, Özlem; Yalçın, Bilgehan; Kale, Gülsev (The Turkish Journal of Pediatrics, 2012)
By comparing our data for the period 1985-2008 with findings from a previous report covering the period 1975-1984, we aimed to share our experience with poisoning cases in order to contribute toward its prevention, diagnosis and treatment. The records of patients admitted to the Pediatric Intensive Care Unit with acute poisoning between November 1985 and October 2008 were evaluated retrospectively. The records of 2251 patients with acute poisoning could be retrieved. Poisoning mostly occurred in the home (92%), via the oral route (92.5%) and by a single intoxicant (81.3%). Two distinct peaks were observed: in boys between 1-5 years of age and in girls between 13-16 years of age. It was noted that 67.4% of poisoning cases were accidental, whereas 25.9% were suicidal and 6.7% were a result of a therapeutic error. Nearly two-thirds (64%) of cases were drug-related, while 36% were non-drug-related. Analgesics-antipyretics ranked first among the drug-related cases, whereas ingestion of a corrosive substance was most common among cases with non-drug poisoning. Colchicine was associated with the highest fatality, while among the causes of non-drug poisoning, carbon monoxide was the deadliest. The overall mortality rate in this study was 1.9%. Mortality from non-drug poisoning was higher than from drug-related causes (3.9% vs. 1.3%). Almost all cases of poisoning below the age of 6 years are potentially preventable. The results of this study highlight the need for reforms in industrial and health policies, with the aim of increasing awareness regarding potential toxins, appropriate storage of potential toxins, and general precautions to promote safety in the home.